ADVANCES IN THE SURGICAL MANAGEMENT OF GASTRIC CANCER: MINIMALLY INVASIVE TECHNIQUES VERSUS CONVENTIONAL APPROACHES - Guimarães, Nicolly Thomas; Moreira, Gustavo Ferreira; de Morais, Rian Barreto Arrais Rodrigues; Camurça, Leonardo Torres; Castilho, Giovana Kadri; Hildefonso, Diogo Mariano; Cemin, Nádia Larissa Souza; Ferreira, Maurício Menezes; Fernandes, José Guilherme Gomes Medeiros; Fonseca, Arnoldo Alves; Lima Junior, Givaldo de Alencar; Viali, Karollyne Henriques Lopes; et al. (Seven Editora, 2025)
Gastric cancer represents one of the main causes of mortality from neoplasms in the world, especially in developing countries. This study aims to compare clinical, oncological, and quality of life outcomes between minimally invasive surgical techniques, such as laparoscopic and robotic gastrectomy, and the conventional open approach in gastric cancer management. A narrative review of the literature was carried out, using databases such as PubMed, Embase, Cochrane Library and SciELO. Studies published in the last ten years that comparatively addressed the different surgical techniques in patients with early and advanced gastric cancer were selected. Inclusion criteria were randomized clinical trials, systematic reviews, and meta-analyses focusing on perioperative, oncological, and quality of life outcomes. Descriptive studies or studies with a small number of cases were excluded. The data were analyzed descriptively, synthesizing information on intraoperative blood loss, length of hospital stay, postoperative complications, recurrence rates, and overall survival. The results showed that minimally invasive techniques have significant benefits in short-term outcomes, such as less surgical trauma, reduced blood loss, and faster recovery. Robotic gastrectomy demonstrated advantages in surgical precision and greater lymph node dissection, while laparoscopic gastrectomy stood out for its economic viability. Long-term oncological outcomes were equivalent between techniques, reinforcing the safety of minimally invasive approaches. However, barriers such as high costs and the long learning curve limit its large-scale implementation. It is concluded that minimally invasive techniques are safe and effective in the management of gastric cancer, and greater training and technological accessibility are needed to expand their application, especially in developing countries. DOI: https://doi.org/10.56238/sevened2024.037-170